Sintered NbO powders for electronic device applications - Nico, C.
Wide band gap niobium oxides are particularly important for electronic device applications. Two types of NbO powders were sintered between 300 and 1100 °C. The structural characterization of the pellets, performed by X-ray diffraction measurements and Raman spectroscopy, revealed the appearance of the NbO and T-, B-, and H-Nb2O5 polymorphs, depending on the sintering temperature. The optical characterization was complemented with absorption measurements and photoluminescence, where it was possible to identify a bandgap of 3.5 eV. A strong dependence of luminescence on the sintering temperature and therefore of the niobium oxide crystalline phases nature was observed. The influence of the morphological and structural characteristics on the dielectrical properties, at room temperature and in the low frequency range (<100 MHz), was studied. The sample with the H-Nb2O5 polymorph presents higher dielectric constant (55) than the samples with T- and B-Nb2O5 (25).